Ambassadors of realpolitik : Sweden, the CSCE and the Cold War - Makko, Aryo (Studies in contemporary European history, 2017)
During the Cold War, Sweden actively cultivated a reputation as the "conscience of the world," working to build bridges between East and West and embracing a nominal commitment to international solidarity. This groundbreaking study explores the tension between realism and idealism in Swedish diplomacy during a key episode in Cold War history-the Conference on Security and Cooperation in Europe, culminating in the 1975 Helsinki Accords. Through careful analysis of new evidence, it offers a compelling counternarrative of this period, showing that Sweden strategically ignored human rights violations in Eastern Europe and the nonaligned states in its pursuit of national interests